1993
DOI: 10.1002/dc.2840090209
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytodiagnosis of breast masses in pregnant and lactating women and its impact on management

Abstract: We reviewed our experience with 9,726 cases of fine-needle aspiration cytology of the breast that were done from January 1983 to February 1992. During our review, we found that 214 aspirates had been submitted from pregnant and lactating women for the investigation of breast mass(es). Despite a variable clinical presentation and spectrum of cytologic findings, we considered the application of aspiration cytology in these women as useful as in the nonpregnant-nonlactating women for management decision. A team a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…FNAC in pregnant and/or lactating women has a higher incidence of FP and FN diagnosis than in nonpregnant/lactating women [29,30,31,32,33]. FP results are due to the fact that the hormonal milieu of pregnancy and lactation leads to epithelial hyperplastic changes with cytologic atypia that can be readily misinterpreted as malignant.…”
Section: Clinical and Cytologic Mimickers Of Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…FNAC in pregnant and/or lactating women has a higher incidence of FP and FN diagnosis than in nonpregnant/lactating women [29,30,31,32,33]. FP results are due to the fact that the hormonal milieu of pregnancy and lactation leads to epithelial hyperplastic changes with cytologic atypia that can be readily misinterpreted as malignant.…”
Section: Clinical and Cytologic Mimickers Of Malignancymentioning
confidence: 99%
“…2). As highlighted by Gupta et al [32], a team approach with close clinical correlation and follow-up made FNAC in pregnant women as useful as in nonpregnant women.…”
Section: Clinical and Cytologic Mimickers Of Malignancymentioning
confidence: 99%
“…An experienced cytopathologist with specific knowledge of the pregnancy is required to avoid false-positive diagnosis. In this setting, core biopsy represents an effective alternative and is mandatory if malignancy is suspected (21,22).…”
Section: Cytologic Analysismentioning
confidence: 99%
“…Historically pregnancy-related hyperplastic changes with atypia were thought to result in false-positive FNA results; however, several authors have demonstrated marked accuracy and a reduction in surgical biopsy rates when performed by a skilled pathologist made aware of the patient's pregnant or lactating state [38][39][40][41]. Core needle and excisional biopsy may be employed also.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%